The Effect of Bullying on Depression in Adolescents: A Meta-Analysis - Fitriah Fitriah; Bhisma Murti; Didik Gunawan Tamtomo (Journal of Health Promotion and Behavior, 2021)
Background: Bullying can cause feelings of insecurity in adolescents with reduced social support and the need for acceptance in the environment and peers is not fulfilled. 16.8% of teenagers who are involved in cyberbullying have a risk of depression. Depressive disorders are common in adolescents, with a prevalence approaching 5.6% in adulthood. This study aims to examine the effect of bullying on depression in adolescents.Subjects and Method: This research is a meta-analytical study and a systematic review. The articles used were obtained from several electronic databases including PubMed, Science Direct and ProQuest. The articles used in this study are articles that have been published from 2010-2021. The research data search process used the search words “bullying and depression”, “bullying and depression and adolescent and cross-sectional study”, “bullying and depression and adolescent and cross-sectional study and adjusted odd ratio”.Results: The results of the meta-analysis study in this study contained 9 articles consisting of Saudi Arabia, Malaysia, Seychelles, United States, Massachusetts, Bosnia and Canada. Bullying can increase the risk of depressive disorder in adolescents (aOR= 2.43; 95% CI= 1.87 to 3.15; p<0.001).Conclusion: Bullying affects the risk of depression in adolescents.Keywords: teens, bullying, depressionCorrespondence: Fitriah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: fitriahbaharuddin@gmail.com. Mobile: +6282350701936.Journal of Health Promotion and Behavior (2021), 06(02): 112-121DOI: https://doi.org/10.26911/thejhpb.2021.06.02.04